2008
DOI: 10.1017/s0022112008000840
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds stresses and mean fields generated by pure waves: applications to shear flows and convection in a rotating shell

Abstract: A general reformulation of the Reynolds stresses created by two-dimensional waves breaking a translational or a rotational invariance is described. This reformulation emphasizes the importance of a geometrical factor: the slope of the separatrices of the wave flow. Its physical relevance is illustrated by two model systems: waves destabilizing open shear flows; and thermal Rossby waves in spherical shell convection with rotation. In the case of shear-flow waves, a new expression of the Reynolds-Orr amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(104 reference statements)
1
20
0
Order By: Relevance
“…Our result of the conventional Poiseuille flow (blue solid curve in figure 12(a)) is in very good accordance with that shown in Plaut et al (2008) for Poiseuille flow with fixed flow rate. We see thatψ 20 for Poiseuille flow is symmetric with respect to the channel centreline and that the nonlinearity mildly accelerates the laminar flow near to the walls, drastically accelerates the flow around the centre of the channel and decelerates the flow in between around y = ±0.8.…”
Section: High Re Cross-flow: Base Flow Modificationsupporting
confidence: 90%
See 1 more Smart Citation
“…Our result of the conventional Poiseuille flow (blue solid curve in figure 12(a)) is in very good accordance with that shown in Plaut et al (2008) for Poiseuille flow with fixed flow rate. We see thatψ 20 for Poiseuille flow is symmetric with respect to the channel centreline and that the nonlinearity mildly accelerates the laminar flow near to the walls, drastically accelerates the flow around the centre of the channel and decelerates the flow in between around y = ±0.8.…”
Section: High Re Cross-flow: Base Flow Modificationsupporting
confidence: 90%
“…The base flow modificationψ 20 (note the relation that u = ψ ) has been discussed in the context of, for example, Poiseuille flow (Plaut et al 2008) and non-Newtonian channel flow (Chekila et al 2011). For hydrostatic EHD flow, the base flow modificatioñ ψ 20 = 0 asŪ = 0, thus we will only discuss it below in the cross-flow case.…”
Section: Modification Of Base Electric Fieldmentioning
confidence: 99%
“…Aubert et al 2003;Gillet & Jones 2006;Calkins et al 2012;Teed et al 2012;Guervilly & Cardin 2017) have been found to compare favourably to 3-D direct numerical simulations in spherical geometry (e.g. Aubert et al 2003;Schaeffer & Cardin 2005a;Plaut et al 2008). This indicates that such 2-D spherical QG models could be efficiently used to explore the turbulent QG regime of convection with E < 10 −8 and Re 10 5 , a parameter regime currently inaccessible to 3-D computations.…”
Section: Introductionmentioning
confidence: 94%
“…The main force balance is between the pressure gradient and the Coriolis force, fulfilling the Taylor-Proudman theorem and establishing the so-called geostrophic state. A mean tilt of the columns in azimuthal direction gives rise to a statistical correlation of non-axisymmetric flows and thus leads to Reynolds stresses that drive the zonal wind system (Busse, 1983;Christensen, 2002;Busse, 2002;Plaut et al, 2008). The typical prograde tilt of the spiralling convective columns establishes a positive flux of angular momentum towards the equatorial region that maintains the dominant prograde equatorial jet (Zhang, 1992;Christensen, 2001).…”
Section: Introductionmentioning
confidence: 99%